Recognition and Treatment of a Right Ventricular Air Embolism - Leon Sun; Katherine I. Harris (Annals of Internal Medicine: Clinical Cases)
Right ventricular air embolism is a rare and dangerous condition that frequently presents with nonspecific symptoms, making diagnosis difficult. We present a case involving a young woman with concerning symptoms following routine injection of contrast. Computed tomography scan visualizing the heart confirmed the finding of a large air embolism. We describe the immediate actions taken and the subsequent treatment provided.